The Properties of Aloe Vera Powder using Cassava Maltodextrin as Carrier Agents - Maherawati Maherawati; Lucky Hartanti (Balai Besar Industri Hasil Perkebunan, 2019)
The aims of this research is to determine the powder properties of aloe vera powder in different amount of cassava maltodextrin addition. The total soluble solid in aloe vera extract before spray drying was adjusted to the total soluble solid as 20%, 25%, and 30% (w/v) by adding the appropriate amount of cassava maltodextrin as carrier agents. The results showed that all aloe vera powder has the water activity in the range of safe water activity for dried food (0.32-0.38). The highest cassava maltodextrin added produce aloe vera powder with the lowest water content (4.49%). The addition of cassava maltodextrin increased brightness, reduced the water content, decreased the cohesiveness between powder particles and increased the flowability of the aloe vera powder. More of cassava maltodextrin addition caused a decrease in solubility and wettability time on aloe vera powder. The aloe vera powder particle had a round shape and uniform size. The higher cassava maltodextrin addition made a larger size of aloe vera powder particle.